Social media marketing and its impact on customer based brand equity of luxury fashion products - Moorjani, Shivani (2013)
Luxury companies have recently started using social media platforms to reach their customers, increase brand awareness, encourage brand loyalty, improve perception of perceived quality and therefore enhance brand equity. Companies have the ability to reach millions of people through these online media; however, they do not have complete control over this new tool of communication since consumers around the world actively engage in the use of Internet to follow, like, share or comment about brands. The purpose of this study is to correct the identified gaps in literature about the ways in which social media communications (firm created and user generated) affect customer based brand equity of luxury fashion products. In order to do so, the social media activities of Gucci, a luxury fashion company, in the United Arab Emirates are analyzed. Yoo & Donthu’s (2001) scale to measure brand equity is used along with Bruhn et al’s (2012) scale to identify this impact. The findings reveal that social media activities positively impact brand awareness, perceived quality, and brand loyalty and therefore enhance customer based brand equity. It also shows that in the Arab culture, brand loyalty is highly essential in order to enhance brand equity. This study offers valuable insights for marketers of luxury brands looking to invest in social media activities to promote their brand in the UAE.